Performance Analysis of Double-MIMO Free Space Optical System under Atmospheric Turbulence - Tom, A. L.; Abdul Rahman, Kram; Tamrin, K. F.; Sahari, S.K.; Nurdiani, Zamhari (2021)
Over the last few years, free space optical communication (FSO) has emerged as a viable alternative to radio frequency communication. It provides a promising high-speed pointto-point communication solution. However, atmospheric absorption, scattering and turbulence degrade wireless optical communication significantly, lowering device efficiency. The attenuation of signals due to the above atmospheric reasons is another major factor that affects device efficiency. The atmospheric turbulence conditions are observed implemented into different models of FSO systems, such as Single Input Single Output (SISO), Multiple Input Multiple Output (MIMO), Wavelength Division Multiplexing MIMO (WDM-MIMO) and proposed model Double Multiple Input Multiple Output (DMIMO) using the Gamma-Gamma model for a variety of reasons. The OptiSystem 7.0 software was used to run simulations to study how various weather conditions (clear, haze and fog) affected the performance of the channel. Simulation results show that implementing Double Multiple Input Multiple Output (DMIMO) techniques for FSO systems provides high quality factor for various ranges while still achieving accurate transmitted data at the receiver side. In the presence of atmospheric turbulence conditions such as clear air, haze and fog, performance improvements signal power levels, quality factor and link distance range have been demonstrated.